Optimizing the Security of Letter of Credit Transactions: Application of Blockchain Technology in Reducing the Risk of Fraud in Banking - C Rantung, Melinda; Siagian, Harlyn; Gallena Sinaga, Judith Tagal (Dinasti International Journal of Economics, Finance & Accounting, 2024)
Letter of Credit (LC) transactions play a vital role in facilitating international trade, but are vulnerable to various forms of fraud such as forgery of documents and manipulation of information. In the banking context, ensuring the security of LC transactions is an urgent challenge. This research aims to investigate the potential of applying blockchain technology in improving the security of LC transactions and reducing the risk of fraud in the banking sector. This research is included in descriptive quantitative research. This research was conducted at Banks in DKI Jakarta. The population in this research are customers who use Letter of Credit transactions. The sampling technique in this research is purposive sampling so that in this research the research sample was 100 customers who used letter of credit transactions. The data analysis technique in this research uses Partial Least Square (PLS). The research results show that blockchain technology has great potential to increase the security of LC transactions through aspects such as high data security, transparency and auditability, as well as automation through smart contracts. With proper implementation, blockchain technology can help reduce the risk of fraud, increase operational efficiency, and build trust in international trade. This study contributes to the understanding of the potential application of blockchain technology in the global financial context and highlights the importance of cross-sector collaboration to address transaction security challenges.